Effects of Bacillus sp. and Lactobacillus sp. combination as a water additive on the culture pond water and growth performance of hybrid grouper (Epinephelus fuscoguttatus × Epinephelus polyphekadion) - Huang, Jianpeng; Amenyogbe, Eric; Ou, Guanghai; Li, Yu; Wen, Zhenwei; Jiang, Xingtao; Chen, Gang (Frontiers in Marine Science, 2022)
The individual Probiotic application has become increasingly widespread in aquaculture and has been extensively studied. However, investigating probiotics as water additives in the grouper culture is still lacking. This study evaluated the functional efficacy of the Bacillus subtilis CICC 10071 (3 × 1011 CFU / g) and Lactobacillus sp. (8 × 1011 CFU / g) combination in a 1:1 ratio on the rearing water quality, water microbial community structure, and growth performance of hybrid grouper. Depending on the additive concentrations of probiotics, we designed four groups, each in triplicate: control (WT, 0g/m3), low concentration (WL, 0.038g/m3), middle concentration (WM, 0.075g/m3), and high concentration (WH, 0.113g/m3). The result shows that throughout the 22-day feeding period, the water supplementation of probiotics significantly decreased Ammonia (NH3) and nitrite (NO2-) in culture water. Final weight (FW), Specific growth rate (SGR), and Weight gain rate (WGR) in treated groups were higher than that in the control group (P<0.05). Analysis of water microbiota revealed that the dominant phylum Bacteroidetes, Proteobacteria, Cyanobacteria, and Actinobacteria enriched in the culture water. Furthermore, we found that the Probiotics combination could significantly reduce the abundance of Cetobacterium (phyla Fusobacteria) related to ammonia and nitrite. The Phylogenetic Investigation of Communities by Reconstruction of Unobserved States 2 (PICRUSt2) also shows that the 'metabolism of other amino acids and ‘Fatty acid biosynthesis’ functions of water microbiota were reinforced by the addition of the probiotic combination. Thus, the probiotic combination exhibited a range of advantages in the grouper culture environment, and further in-depth studies are needed.